Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1997
DOI: 10.1121/1.419904
|View full text |Cite
|
Sign up to set email alerts
|

Measurements of small-caliber ballistic shock waves in air

Abstract: Megahertz bandwidth pressure measurements of airborne ballistic shock waves from bullets are presented which confirm weak-shock theoretical predictions of waveform shape, period, amplitude, and the scaling of these quantities with shock propagation distance. Wavefront distortions and amplitude variations are quantified versus shock propagation distances of 3-55 m and agree with predictions based on linear acoustic propagation through simple turbulence models. Observed rise times probably exhibit a mix of turbu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(36 citation statements)
references
References 13 publications
(25 reference statements)
0
36
0
Order By: Relevance
“…Fansler's work gives a good idea of the ideal muzzle blast pressure wave without contamination from echoes or propagation effects [4]. Experiments with greater distances from the muzzle were conducted by Stoughton [18]. The measurements of the ballistic shockwaves using calibrated pressure transducers at known locations, measured bullet speeds, and miss distances of 3 -55 meters for 5.56 mm and 7.62 mm projectiles were made.…”
Section: Related Workmentioning
confidence: 99%
“…Fansler's work gives a good idea of the ideal muzzle blast pressure wave without contamination from echoes or propagation effects [4]. Experiments with greater distances from the muzzle were conducted by Stoughton [18]. The measurements of the ballistic shockwaves using calibrated pressure transducers at known locations, measured bullet speeds, and miss distances of 3 -55 meters for 5.56 mm and 7.62 mm projectiles were made.…”
Section: Related Workmentioning
confidence: 99%
“…The non-linear propagation behavior of the shock wave will gradually lose its characteristic "N" wave shape and become a less abrupt "S" shaped pressure disturbance due to nonlinear dispersion [5].…”
Section: Acoustical Issuesmentioning
confidence: 99%
“…If a supersonic projectile's journey from the firearm to the target is more than a few tens of meters, the effects of drag-induced deceleration may need to be taken into account [4,5]. The bullet is slowed by friction with the air and due to the conversion of its kinetic energy into the acoustic shock wave.…”
Section: Ground Surfacementioning
confidence: 99%
“…In the existing literature, the initial establishment of the theory of shockwave model provides the basis for the prediction of the overpressure and the drawing of the contour line of the shockwave overpressure field [1]. Previous studies showed that the test of the shockwave overpressure field to obtain the overpressure value of the sensor array at different points and draw the contour lines by the interpolation algorithm was mainly based on the electric method [2]. Interpolation compensates for the deficiency of spatial observation data points.…”
Section: Introductionmentioning
confidence: 99%